Bivalent histone modifications during tooth development - Zheng, Li-Wei (Int J Oral Sci, 2014)
Histone methylation is one of the most widely studied post-transcriptional modifications. It is thought to be an important epigenetic event that is closely associated with cell fate determination and differentiation. To explore the spatiotemporal expression of histone H3 lysine 4 trimethylation (H3K4me3) and histone H3 lysine 27 trimethylation (H3K27me3) epigenetic marks and methylation or demethylation transferases in tooth organ development, we measured the expression of SET7, EZH2, KDM5B and JMJD3 via immunohistochemistry and quantitative polymerase chain reaction (qPCR) analysis in the first molar of BALB/c mice embryos at E13.5, E15.5, E17.5, P0 and P3, respectively. We also measured the expression of H3K4me3 and H3K27me3 with immunofluorescence staining. During murine tooth germ development, methylation or demethylation transferases were expressed in a spatial–temporal manner. The bivalent modification characterized by H3K4me3 and H3K27me3 can be found during the tooth germ development, as shown by immunofluorescence. The expression of SET7, EZH2 as methylation transferases and KDM5B and JMJD3 as demethylation transferases indicated accordingly with the expression of H3K4me3 and H3K27me3 respectively to some extent. The bivalent histone may play a critical role in tooth organ development via the regulation of cell differentiation.